ANALISIS EFEKTIVITAS DAN PRAKTIKALITAS PENGGUNAAN SPECIAL SERVICE TOOL (SST) PEMBUKA PEGAS KATUP BERBASIS PNEUMATIK UNTUK PENGGANTIAN SEAL KATUP TANPA MELEPAS KEPALA SILINDER - Ikram; Hasan Maksum; Rifdarmon; Muslim (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effectiveness and practicality of using a pneumatic valve spring remover Special Service Tool (SST) in the valve seal replacement process without removing the cylinder head, and to compare it with the conventional method. The experiment involved two groups: the experimental group using the pneumatic SST and the control group using the conventional method. The results showed that the pneumatic SST reduced the work time by 31.9%, from 433.78 minutes to 295.33 minutes. Additionally, the Post-Study System Usability Questionnaire (PSSUQ) revealed excellent scores for system usefulness (1.35), information quality (1.96), interface quality (1.74), and overall satisfaction (1.66), indicating that the pneumatic SST is not only time-effective but also practical and comfortable to use. Based on these results, the pneumatic SST is recommended as an efficient and easy-to-operate tool for vehicle maintenance in workshops.